SOSIALISASI PROGRAM PEMBERDAYAAN UMKM DENGAN SISTEM DIGITAL GUNA MENINGKATKAN DAYA SAING DI DESA KOTARINDAU - Rachmad Rachmad; Askar Mayusa; Meldi Amijaya; Yulizar Pramudika; Dandan Haryono (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This community service activity aims to increase the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Kotarindau Village through the use of digital systems. Technological developments require MSMEs to adapt to increasingly competitive market changes, particularly in marketing, management, and business administration. Through a socialization program, the community service team provides assistance in the form of training on the use of digital platforms, online marketing strategies, and application-based financial management. The methods used include counseling, live demonstrations, and interactive discussions with MSMEs. The results of the activity indicate an increase in community understanding and skills in utilizing digital technology as a means of promotion, transactions, and business development. Thus, this program is expected to encourage the independence of MSMEs in Kotarindau Village and expand market reach, thereby increasing the competitiveness of local products.